Federal President Frank-Walter Steinmeier at the opening of the Alexander von Humboldt Season in Quito, Ecuador, on 13 February 2019 (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2019)
No abstract available.